Secretome analysis of Trypanosoma cruzi by proteomics studies - Brossas, Jean Yves (2017)
Background: Chagas disease is a debilitating often fatal disease resulting from infection by the protozoan parasite Trypanosoma cruzi. Chagas disease is endemic in 21 countries of the Americas, and it is an emerging disease in other countries as a result of migration. Given the chronic nature of the infection where intracellular parasites persist for years, the diagnosis of T. cruzi by direct detection is difficult, whereas serologic tests though sensitive may yield false-positive results. The development of new rapid test based on the identification of soluble parasitic antigens in serum would be a real innovation in the diagnosis of Chagas disease. Methods: To identify new soluble biomarkers that may improve diagnostic tests, we investigated the proteins secreted by T. cruzi using mass spectrometric analyses of conditioned culture media devoid of serum collected during the emergence of trypomastigotes from infected Vero cells. In addition, we compared the secretomes of two T. cruzi strains from DTU Tc VI (VD and CL Brener). Results: Analysis of the secretome collected during the emergence of trypomastigotes from Vero cells led to the identification of 591 T. cruzi proteins. Three hundred sixty three proteins are common to both strains and most belong to different multigenic super families (i.e. TcS, GP63, MASP, and DGF1). Ultimately we have established a list of 94 secreted proteins, common to both DTU Tc VI strains that do not belong to members of multigene families. Conclusions: This study provides the first comparative analysis of the secretomes from two distinct T. cruzi strains of DTU TcVI. This led us to identify a subset of common secreted proteins that could potentially serve as serum markers for T. cruzi infection. Their potential could now be evaluated, with specific antibodies using sera collected from patients and residents from endemic regions.